Visiting Nurses’ Perceived Difficulties and Corresponding Measures in Providing Practical Guidance during Home-based Nursing Care Practical Training - Tokairin, Miyuki; Furuse, Midori; Morikagi, Yuko; Kobayashi, Atsuko (Journal of Japan Society of Nursing Research, 2019)
Background and purpose: The present study aimed to elucidate visiting nurses' perceived difficulties and corresponding measures in providing practical guidance during home-based nursing care practical training. Method: Participants were 10 visiting nurses. Data were collected through group interviews, and a qualitative descriptive analysis was performed. Results: The following four categories were extracted pertaining to the difficulties perceived by visiting nurses in providing practical guidance during home-based nursing care practical training: the [generation gap] perceived due to the manners of the students, [a sense of burden in accompanying visits], [difficulty in providing practical guidance], and the [anxiety about providing practical guidance on one's own]. The visiting nurses implemented measures such as [understanding the student], [providing guidance according to the student's abilities], [developing new ways to provide guidance], [providing guidance according to the home-based treatment environment], and [connecting the care recipient with the student] to address these difficulties. However, they were unable to resolve the problem of [anxiety about providing practical guidance on one's own]. Conclusion: It was suggest that visiting nurse could recognize the role of the training leader during home-based nursing care practice, and the need of the education support to practice of the training instruction competency as well as role accomplishment.